Enhancing Theological Education for Women in Africa - Mwaniki, Lydia (The Ecumenical Review, 2019)
This paper highlights the models that are being used by African women theologians and the All Africa Conference of Churches to increase women's chances in theological education, hence ensuring equal participation of women and men in church leadership.
paid
Keywords: African women theologians; All Africa Conference of Churches; feminist hermeneutics; theological education